Silk Vista Baby Is a Safe and Technically Feasible Flow Diverting Stent for Distal Aneurysm Treatment - Gavrilovic, Vladimir; Dapoto, Annarita; Marotti, Nicola; Pellegrin, Andrea; Pauro, Alessandro; Vit, Alessandro; Sponza, Massimo (Frontiers in Neurology, 2021)
Background and Purpose: Flow diverting stents are designed to divert blood flow from the aneurysm sac, allowing for eventual occlusion following endovascular therapy. This case series reports clinical experience using the Silk Vista Baby (SVB, Balt Extrusion, Montmorency, France), a flow diverter (FD) designed to treat intracranial aneurysms in small, distal vessels. Methods: All patients who underwent treatment with SVB at the University Hospital "Santa Maria della Misericordia" of Udine between July 2018 and September 2020 were retrospectively identified. Baseline patient and aneurysm characteristics, intraprocedural technical outcomes, periprocedural complications, modified Rankin Scale (mRS) at discharge, magnetic resonance imaging (MRI) results at 3-month follow-up, and angiographic results at 6-month follow-up were collected. Results: A total of 18 patients (55.6% [10/18] male; mean age 62.6 years, range: 42-77 years) were retrospectively identified, receiving treatment for 22 aneurysms. Most patients were symptomatic (14/18, 77.8%) and approximately half had subarachnoid hemorrhage (10/18, 55.6%). Sufficient aneurysm coverage was achieved in 88.9% (16/18) of patients with a single device. Mortality did not occur (0/18, 0%); adverse device-related events included side branch occlusion (1/18, 5.6%) and in-stent thrombosis (1/18, 5.6%). At discharge, 77.8% (14/18) had an mRS of 0. In most cases, patients showed complete occlusion (10/15, 66.7%) or a small aneurysmal remnant (3/15, 20.0%) upon MRI; upon angiography, most showed complete occlusion (10/13, 76.9%) or only a small aneurysmal remnant (2/13, 15.4%). Conclusion: This case series showed that the SVB FD is safe and feasible to use in patients with aneurysms in small, distal vessels. Additional randomized, prospective studies with larger cohorts are needed for the SVB.